Late Payments, Liquidity Constraints and the Mismatch between Due Dates and Paydays - Momi Dahan; Udi Nisan (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines a small random liquidity shock to reveal the effect of liquidity constraints on late payment behavior. In Jerusalem, water bill due dates are randomly determined and therefore may occur just before or after social security paydays. We compared the likelihood of late payments by low-income households when they receive their social benefits a day after the water bill due date to the likelihood of late payment by the same households when they receive their benefits a day or more before the water bill due date. Using a large administrative data set, we found that a small random liquidity shock leads to a substantial increase in late payments of more than 10 percentage points among income support recipients and around 6 percentage points for old-age pension recipients with supplementary income. The mismatch between utility payment due dates and paydays may result in reduced psychological well-being, as well as interest charges and high late fees, contributing to the poverty penalty.
Keywords: I30; L95; D10; 330; late payment; liquidity; poverty penalty; water; social security; paydays